2012
DOI: 10.1542/peds.2011-3848
|View full text |Cite
|
Sign up to set email alerts
|

Sucrose for Procedural Pain Management in Infants

Abstract: The use of oral sucrose has been the most extensively studied pain intervention in newborn care to date. More than 150 published studies relating to sweet-taste-induced calming and analgesia in human infants have been identified, of which 100 (65%) include sucrose. With only a few exceptions, sucrose, glucose, or other sweet solutions reduced pain responses during commonly performed painful procedures in diverse populations of infants up to 12 months of age. Sucrose has been widely recommended for routine use … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
62
0
8

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 99 publications
(71 citation statements)
references
References 74 publications
1
62
0
8
Order By: Relevance
“…It has been extensively studied for this purpose, yet many gaps in knowledge remain, including appropriate dosing, mechanism of action, soothing versus analgesic effects, and long-term consequences. [71][72][73] A meta-analysis of 57 studies including >4730 infants with gestational ages ranging from 25 to 44 weeks concluded that sucrose is safe and effective for reducing procedural pain from a single event. 74 Maximum reductions in physiologic and behavioral pain indicators have been noted when sucrose was administered ∼2 minutes before a painful stimulus, and the effects lasted ∼4 minutes.…”
Section: Pharmacologic Treatment Strategies Sucrose and Glucosementioning
confidence: 99%
See 2 more Smart Citations
“…It has been extensively studied for this purpose, yet many gaps in knowledge remain, including appropriate dosing, mechanism of action, soothing versus analgesic effects, and long-term consequences. [71][72][73] A meta-analysis of 57 studies including >4730 infants with gestational ages ranging from 25 to 44 weeks concluded that sucrose is safe and effective for reducing procedural pain from a single event. 74 Maximum reductions in physiologic and behavioral pain indicators have been noted when sucrose was administered ∼2 minutes before a painful stimulus, and the effects lasted ∼4 minutes.…”
Section: Pharmacologic Treatment Strategies Sucrose and Glucosementioning
confidence: 99%
“…82 Although an optimal dose has not been determined, 74 an oral dose of 0.1 to 1 mL of 24% sucrose (or 0.2-0.5 mL/kg) 2 minutes before a painful procedure has been recommended, taking into account gestational age, severity of illness, and procedure to be performed. 71 The role and safety of long-term sucrose use for persistent, ongoing pain have not been systematically studied. One study in 107 preterm infants of <31 weeks' gestation found worse neurodevelopmental scores at 32, 36, and 40 weeks' gestational age in infants who had received >10 doses of sucrose over a 24-hour period in the first week of life, raising concerns about frequent dosing in newly born preterm infants.…”
Section: Pharmacologic Treatment Strategies Sucrose and Glucosementioning
confidence: 99%
See 1 more Smart Citation
“…[18][19][20] The medical literature has long demonstrated many effective pharmacologic and nonpharmacologic interventions (NPIs) for pediatric pain. 15,[21][22][23][24][25] The frequency and success of application of these interventions by Canadian pediatric emergency physicians has not been reported. The purpose of this study was to describe reported practice patterns for pediatric emergency medicine (PEM) physicians and to explore factors that facilitate or hinder pain management.…”
Section: Ré Sumémentioning
confidence: 99%
“…1 The short-term effects of painful procedures include crying or grimacing, disturbance in sleep or wakefulness state, increased oxygen consumption, ventilation-perfusion mismatch, and increased gastric acidity. [2][3][4] The long-term effects may be an exaggerated response to pain in later infancy 5 and the neurotoxicity of untreated pain in the developing brain. 6 Strong pharmacologic interventions are rarely used during short, minor painful procedures in neonates because of the risk of adverse effects on the newborn's respiratory and central nervous systems.…”
mentioning
confidence: 99%